Immunosuppressant Treatment in Rheumatic Musculoskeletal Diseases Does Not Inhibit Elicitation of Humoral Response to SARS-CoV-2 Infection and Preserves Effector Immune Cell Populations - Favalli, Andrea; Favalli, Ennio Giulio; Gobbini, Andrea; Zagato, Elena; Bombaci, Mauro; Maioli, Gabriella; Pesce, Elisa; Donnici, Lorena; Gruarin, Paola; Biggioggero, Martina; Curti, Serena; Manganaro, Lara; et al. (Frontiers in Immunology, 2022)
COVID-19 has proven to be particularly serious and life-threatening for patients presenting pre-existing pathologies. Patients affected by rheumatic musculoskeletal disease (RMD) are likely to have impaired immune responses against SARS-CoV-2 infection due to their compromised immune system and the prolonged use of disease-modifying anti-rheumatic drugs (DMARDs), which include conventional synthetic (cs) DMARDs or biologic and targeted synthetic (b/ts) DMARDs. Objectives: Our objective is to provide an integrated analysis of the immune response following SARS-CoV-2 in RMD patients treated with different classes of DMARDs and to identify drug-specific effects. Methods: We carried out an immunological analysis of the antibody responses toward SARS-CoV-2 nucleocapsid and RBD proteins elicited in RMD patients treated with different DMARDs, by ELISA and neutralization assays. We have also done an extensive immunophenotypic analysis of the major immune cell populations in RMD patients. Results: We showed that RMD individuals under most DMARD treatments mount a sustained antibody response to the virus, with neutralizing activity. In addition, they induced displayed a sizable percentage of effector T and B lymphocytes. Among b-DMARDs we found that anti-TNFα treatments are more favorable drugs to elicit humoral and cellular immune responses as compared to CTLA4-Ig and anti-IL6R inhibitors. Conclusions: This study provides a whole picture of the humoral and cellular immune responses in RMD patients by reassuring on the use of DMARD treatments during COVID-19. The study points to TNF-inhibitorsas those DMARDs permitting elicitation of functional antibodies to SARS-CoV-2 and adaptive effector populations available to counteract possible re-infections.